Power: divine and human : Christian and Muslim perspectives : a record of the Sixteenth Building Bridges Seminar hosted by Georgetown University, May 8-12, 2017 - Mosher, Lucinda; Marshall, David (Georgetown University Press, 2019)
Overviews -- The power of god and Islam's regime of power on earth / Jonathan Brown -- Religion and power : a Christian perspective / Philip Sheldrake -- Power in Muslim and Christian scriptures -- The contours of god's power : an introduction to passages from the Qur'an and Hadith / Martin Nguyen -- Qur'an and Hadith on god's power : texts for dialogue -- Biblical conceptions of power; divine and human / Stephen Cook -- The Bible on divine and human power : texts for dialogue -- Power and community in Islamic and Christian writings -- Ideals and realities of Muslim community ordering / Ahmet Alibasi -- Islamic texts on ideals and realities of Muslim community ordering -- The community of god's rule : from nation to church / Joan O'Donovan -- Christian texts on the community of god's rule -- Political power and faith -- The role of the community in the broader world : Islamic perspectives / Mahan Mirza -- Islamic texts for dialogue on community in the broader world -- Faith and political power : a "non-establishment" reading of the Christian tradition / Jonathan Chaplin -- Christian texts for dialogue on faith and political power -- Reflections -- Conversations on power : some reflections on Building Bridges Seminar 2017.